DACS-New Amperometric Reagent for Thorium - Lavale, A.K.; Lavele, S.C.; Pitre, K.S. (Asian Journal of Chemistry, 2010)
3-3´ Bis [N-N´ dicarboxy methyl] o-cresol sulphothaleinknown as DACS has been used as reagent for the amperometric titrations of chromium(IV) at pH 3.10 ± 0.02 in Britton-Robinson buffer. The minimum amount of thorium about 10 μg. could be detected successfully with an error less than ± 1.0%. The results of amperometric titrations are also supported by spectral studies. Job's method and mole ratio method were applied to confirm the stoichiometry of thorium: DACS complex formation. The result revealed that 1: 2 complex with stability constant value of log β═6.3 has been formed in the prescribed experimental condition. The effect of diverse ions on the amperometric titration of thorium with DACS revealed that small amount of rare metals and rare earths hampered the titrimetric procedure.